2009
DOI: 10.1002/chem.200900921
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Strain and the Nature of Spin Crossover in Binuclear Complexes: Two‐Step Spin Crossover in a 4,4′‐Bipyridine‐Bridged Iron(II) Complex [{Fe(dpia)(NCS)2}2(4,4′‐bpy)] (dpia=di(2‐picolyl)amine; 4,4′‐bpy=4,4′‐bipyridine)

Abstract: The synthesis and detailed characterization of the new spin crossover (SCO) binuclear complex [{Fe(dpia)(NCS)(2)}(2)(4,4'-bpy)] (1; dpia=di(2-picolyl)amine, 4,4'-bpy = 4,4'-bipyridine) are reported. Variable-temperature magnetic susceptibility measurements show a relatively cooperative two-step spin transition suggesting the occurrence of three spin-state isomers: [HS-HS], [HS-LS], and [LS-LS] (HS: high spin, LS: low spin). A short plateau at 204 K separates the two steps and conforms with about 50% of the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 58 publications
2
31
0
Order By: Relevance
“…7,8 Short-range correlations may also compete with long-range interactions and give rise to deviation from mean-field behaviors, 9 as evidenced in some cases by distinctive long relaxation tails from the LIESST state. 10 Although the vast majority of thermal spin transitions proceed in a single step, there has been an increasing number of two-step transitions reported for polymeric, [11][12][13][14][15][16][17] polynuclear, [18][19][20][21][22][23][24] or mononuclear SCO systems. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Such transitions result most frequently from the existence of two crystallographically (symmetrically) independent SCO Fe I I sites with slightly different coordination environments, leading to dissimilar transition temperatures delimiting a plateau (or shoulder), which usually occurs with an approximately equal populations of HS and LS species.…”
Section: Imentioning
confidence: 99%
“…7,8 Short-range correlations may also compete with long-range interactions and give rise to deviation from mean-field behaviors, 9 as evidenced in some cases by distinctive long relaxation tails from the LIESST state. 10 Although the vast majority of thermal spin transitions proceed in a single step, there has been an increasing number of two-step transitions reported for polymeric, [11][12][13][14][15][16][17] polynuclear, [18][19][20][21][22][23][24] or mononuclear SCO systems. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Such transitions result most frequently from the existence of two crystallographically (symmetrically) independent SCO Fe I I sites with slightly different coordination environments, leading to dissimilar transition temperatures delimiting a plateau (or shoulder), which usually occurs with an approximately equal populations of HS and LS species.…”
Section: Imentioning
confidence: 99%
“…Such differences in susceptibilities as these are not unusual in SCO chemistry and the authors were, of course, keen to find out why such differences occurred. The crystal structures of the dinuclear molecules, and how they packed in the crystal, were discussed in detail, as were the octahedral distortion parameters, (sum of deviations of the 12 cis N-Fe-N angles from 90 • ) for the HS-HS structures, around each Fe II centre, with polymorph 2 having two distinct Fe sites even at 293 K. The 2-step example 1 did not show structurally distinct Fe sites within each binuclear molecule at 183 78 and in other dinuclear SCO compounds having bipyrimidine, pyrazolate, triazolate and dicyanamide bridges. 64 The 'take home' message was that the nature of the spin-transition (full 1-step; full 2-step; half crossover) in dinuclear Fe II SCO compounds was primarily related to the degree of the octahedral distortions at the FeN 6 cores, that is intramolecular effects, these being influenced by packing and ligand strain arising from terminal and/or bridging ligands.…”
Section: Discrete Clusters Of Sco Compoundsmentioning
confidence: 99%
“…Finally, this thorough study showed that the [HS-HS] forms of phases I and (photoexcited/metastable) III * were different. However, the distortion arguments given for the phia analogues 78 4 ] derivative that we structurally characterised at around that time, with L = 1,2,4(N-picoline) remained HS-HS at all temperatures. 83 Recently, Garcia et al reported another such complex, with an imino-substituted triazole, 1,2,4(N=C(C 6 H 4 (2-OH)-triazole).…”
Section: Discrete Clusters Of Sco Compoundsmentioning
confidence: 99%
“…The ligand 4,4 0 -bipyridine is an ideal connector between the transition metal atoms for the propagation of coordination networks due to the following features: it has two potential binding sites which are arranged in a divergent (exo) fashion; has a rigid structure which will help in the predictability of the network geometries; the length of the ligand is good enough to create the cavities of molecular dimensions upon the formation of the networks with metal atoms [18][19][20][21]. Herein, we report the synthesis, crystal structure, infrared spectrum, and thermal behavior of a new one-dimensional copper complex: {[Cu(NAP) 2 ](4,4 0 -bpy) 1/2 }Á DMF (NAPH = a-naphthoic acid, 4,4 0 -bpy = 4,4 0 -bipyridine), with neutral naphthalene-carboxylate paddle-wheel binuclear units [Cu 2 (NAP) 4 ] and the rigid linear bidentate bridging ligand 4,4 0 -bipyridine.…”
Section: Introductionmentioning
confidence: 99%